2012
DOI: 10.1590/s1516-35982012001000011
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical quality of sanitized commercial eggs experimentally contaminated with Pseudomonas aeruginosa and refrigerated during storage

Abstract: -The objective of this study to verify the physicochemical quality of commercial washed and unwashed eggs, experimentally inoculated on the shell with Pseudomonas aeruginosa and stored at 5 and 25 o C for 30 days. A total of 384 eggs, classified as large, from light Dekalb White laying hens at 30 to 40 weeks of age, were used. The experimental design consisted of two blocks in a 2 × 2 × 2 factorial arrangement (contamination, washing, and refrigeration) with six replicates. The sanitization was performed by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
4
0
3
Order By: Relevance
“…In a study related to the color values of egg yolk, it was found that the levels of brightness (L) and yellowness (b) were higher in organic eggs, and that the level of redness (a) was low (Hidalgo et al, 2008). in foods and can affect the deterioration of the product (Mendes et al, 2012). It was determined that there was an increase in TAPB counts from summer to winter in all of the samples (p < .05).…”
Section: Color Propertiesmentioning
confidence: 93%
“…In a study related to the color values of egg yolk, it was found that the levels of brightness (L) and yellowness (b) were higher in organic eggs, and that the level of redness (a) was low (Hidalgo et al, 2008). in foods and can affect the deterioration of the product (Mendes et al, 2012). It was determined that there was an increase in TAPB counts from summer to winter in all of the samples (p < .05).…”
Section: Color Propertiesmentioning
confidence: 93%
“…Mendes i wsp. [9] oceniali jakość jaj w zależności m.in. od temperatury przechowywania i sanityzacji.…”
Section: Wyniki I Dyskusjaunclassified
“…The consumer's first impression of table eggs at purchase is based on freshness or physical perceptions (qualities) like soundness of shell, shape, texture, color, and cleanliness [2]. Unlike external quality, the internal quality of an egg begins to decline soon after it is laid; factors associated with management, nutrition, handling, and storage conditions (time and temperature) affect the egg's internal quality [3,4]. The internal quality of an egg is linked to albumen and its relative viscosity, shape and firmness of yolk, depth of air cell, presence or absence of meat and blood spots, pH, and Haugh unit (HU); among these, the Haugh unit has been construed as a standard for the determination of the internal quality of an egg.…”
Section: Introductionmentioning
confidence: 99%